Ketamine inhibits neuronal differentiation by regulating brain-derived neurotrophic factor (BDNF) signaling. (April 2021) - Liu, Sheng; Tao, Guorong; Zhou, Changsheng; Wang, Qingxiu; Wang, Wei; Fei, Xuejie
Abstract: Ketamine is widely used in pediatric anesthesia, perioperative sedation, and analgesia. Knowledge of anesthesia neurotoxicity in humans is currently limited by the difficulty of obtaining neurons and performing developmental toxicity studies in fetal and pediatric populations. However, mouse embryonic stem cells (mESCs) derived from embryos at the preimplantation stage demonstrate an unlimited ability to self-renew and generate different cell types and are a valuable tool for clinical research. Thus, in this study, a model was employed to investigate the mechanism by which ketamine (200 nM) influences the neuronal differentiation of mESCs. Mouse ESCs were treated with an anesthetic dose of ketamine, and neuronal differentiation was significantly inhibited on day 5. Downregulation of brain-derived neurotrophic factor (BDNF) by shRNA was found to have the same inhibitory effect. Furthermore, a rescue experiment indicated that BDNF overexpression markedly restored the neuronal differentiation inhibited by ketamine in the ketamine/BDNF group on day 5. Taken together, these data suggested that ketamine inhibited the neuronal differentiation of mESCs, possibly by interfering with BDNF. The results of the current study may provide novel ideas for preventing ketamine toxicity in the developing fetus. Highlights: Ketamine significantly inhibited the neuronal differentiation. Inhibition of BDNF significantly repressed the neuronal differentiation. Overexpression of BDNF significantly mitigated the inhibition of neuronal differentiation induced by ketamine. Ketamine inhibits neuronal differentiation of mESCs possibly by interfering with BDNF signaling.